1990
DOI: 10.1007/bf00917453
|View full text |Cite
|
Sign up to set email alerts
|

Colonic inflammation in the rabbit induced by phorbol-12-myristate-13-acetate

Abstract: Neutrophil (PMNL) infiltration of inflamed colonic tissue is a prominent feature of human inflammatory bowel disease (IBD). Colitis was established in New Zealand white rabbits by the intrarectal instillation of 1.5 mg/kg (in 10 ml 20% ethanol) phorbol-12-myristate-13-acetate (PMA) and assessed by visual grading of colonic inflammation, levels of the neutrophil marker enzyme myeloperoxidase (MPO), and histological examination. After 24 h there was a significant (P less than 0.001) increase in MPO levels in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…to induce colitis in both rabbits and rats (41,42). Caco-2 cells were treated for 0, 4, and 16 h with 50 ng/ml PMA or vehicle control.…”
Section: Resultsmentioning
confidence: 99%
“…to induce colitis in both rabbits and rats (41,42). Caco-2 cells were treated for 0, 4, and 16 h with 50 ng/ml PMA or vehicle control.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction was then stirred at room temperature for 2 h. The reaction solution was diluted with Et20, washed with H20 and brine, and dried (MgS04). Purification by flash column chromatography (3% EtOAc in hexane) provided 24.9 g (93%) of 13 as a colorless oil: NMR (250 MHz, CDCI3) 7.7 (d, 4H, aryl), 7.4 (m, 6H, aryl), 3.63 (t, 2H, OCH2), 2.23 (m, 2H, CH2), 1.97 (t, 1H, acetylenic), 1.6-1.3 (m, 8H, (CH2)4), 1.05 (s, 9H, ferí-butyl); IR (film) vmax 3321, 2940, 2125 cm"1.…”
Section: Methodsmentioning
confidence: 99%
“…This compound has recently evolved into the xanthone LY292728 (3) having a K\ of 0.47 nM in human PMNs.11 Ono reported that (4) has a A) of 4 nM for LTB4 receptors on human PMNs12 while Roche has reported a related compound, Ro-25-3562 (5), as having a K of 1 nM. 13 The chiral LTB4 receptor antagonist SC-53228 (6, K = 1.3 nM) has been reported by Searle,14 and Rhdne-Poulenc Rorer has reported that RG 14893 (7) has a K of 2 nM on human PMNs. 15 The LTB4 receptor antagonist effort was initiated with the objective to discover novel antiinflammatory agents.…”
mentioning
confidence: 98%
“…We add the references (if found) for the selected metabolites. [Solakivi et al, 2011] Docosahexaenoate [Solakivi et al, 2011] Dodecanedioate [Lee et al, 2017] Phenyllactate [Lavelle and Sokol, 2020] Eicosatrienoate [Kuroki et al, 1997] Olmesartan [Saber et al, 2019] Taurolithocholate [Bauset et al, 2021] Eicosapentaenoate [Kuroki et al, 1997] Arachidonate [Lloyd-Price et al, 2019] Myristate [Fretland et al, 1990] Tetradecanedioate -Porphobilinogen -Masilinate -…”
Section: Acknowledgementmentioning
confidence: 99%